The Effect of Problem Construction on Team Process and Creativity - Reiter-Palmon, Roni; Murugavel, Vignesh (Frontiers in Psychology, 2018)
Although research on the benefits of problem construction within the creative process is expanding, research on team problem construction is limited. This study investigates the cognitive process of problem construction and identification at the team level through an experimental design. Furthermore, this study explores team social processes in relation to problem construction instructions. Using student teams solving a real-world problem, the results of this study revealed that teams that engaged in problem construction and identification generated more original ideas. Moreover, higher satisfaction and lower conflict was observed among groups that engaged in problem construction. These findings highlight the utility of problem construction for teams engaging in creative problem-solving.